The over-population fallacy considered - Lawson, James A. (Statistical and Social Inquiry Society of Ireland, 1851)
We hear so much at the present day about over-population and the remedies suggested for that disease, that I think it will not be uninteresting to inquire what over-population is, when it can properly be said to exist, and how we are to determine whether it does exist in a country. The question of over-population I propose to treat this evening merely in an economic view, in order to determine the proper meaning and application of the word, and to point out the circumstances which indicate its existence. It admits of course of being treated as a statistical question, by ascertaining from actual returns the number, and by comparison with previous returns the rate of increase, of the population, and deriving from other returns the rate of production of these commodities which the population consumed. An inquiry of that kind, properly conducted, would be most important, as showing the relative growths of population and subsistence in any country. It is not my design to enter into, that question at present; and, indeed, in order to derive the full benefit from such an inquiry, we should in the first instance investigate some of the abstract relations between population and subsistence.
Read November 19th 1849
Keywords: Overpopulation; Productive capacity; 314.15